1998
DOI: 10.1088/0953-2048/11/10/031
|View full text |Cite
|
Sign up to set email alerts
|

Transport ac losses of multifilament Ag-sheathed Bi-2223 tapes with periodically arranged filaments in the configuration

Abstract: The powder-in-tube route for fabricating long lengths of multifilament Ag-sheathed Bi-2223 tape can be used to manufacture tapes with a variety of filamentary configurations. The design of the filament array within a tape will influence the electrical properties including the ac loss which becomes a significant consideration when designing a closed cooling system. The effect of periodically arranged filaments on the transport ac losses of Bi-2223 tapes has been investigated and the results compared with the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The columnar structure as used in sample A is expected to depress transport ac losses at low currents. In some studies this expectation has been confirmed [3,4], however in other cases no effect on ac losses [5] or even an increase at low currents was observed [6]. This can also be related to the uniformity of single filaments.…”
Section: Samplesmentioning
confidence: 86%
“…The columnar structure as used in sample A is expected to depress transport ac losses at low currents. In some studies this expectation has been confirmed [3,4], however in other cases no effect on ac losses [5] or even an increase at low currents was observed [6]. This can also be related to the uniformity of single filaments.…”
Section: Samplesmentioning
confidence: 86%